Activation of IL‐27 signalling promotes development of postinfluenza pneumococcal pneumonia. Issue 1 (29th October 2013) - Cao, Ju; Wang, Dongsheng; Xu, Fang; Gong, Yi; Wang, Hong; Song, Zixin; Li, Dageng; Zhang, Hua; Li, Dairong; Zhang, Liping; Xia, Yun; Xu, Huajian; et al.
Abstract Postinfluenza pneumococcal pneumonia is a common cause of death in humans. However, the role of IL‐27 in the pathogenesis of secondary pneumococcal pneumonia after influenza is unknown. We now report that influenza infection induced pulmonary IL‐27 production in a type I IFN‐α/β receptor (IFNAR) signalling‐dependent manner, which sensitized mice to secondary pneumococcal infection downstream of IFNAR pathway. Mice deficient in IL‐27 receptor were resistant to secondary pneumococcal infection and generated more IL‐17A‐producing γδ T cells but not αβ T cells, thereby leading to enhanced neutrophil response during the early phase of host defence. IL‐27 treatment could suppress the development of IL‐17A‐producing γδ T cells activated by Streptococcus pneumoniae and dendritic cells. This suppressive activity of IL‐27 on γδ T cells was dependent on transcription factor STAT1. Finally, neutralization of IL‐27 or administration of IL‐17A restored the role of γδ T cells in combating secondary pneumococcal infection. Our study defines what we believe to be a novel role of IL‐27 in impairing host innate immunity against pneumococcal infection.